2020
DOI: 10.1093/pm/pnaa233
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Postoperative Opioid Use After Elective Spine and Peripheral Nerve Surgery Using an Enhanced Recovery After Surgery Program

Abstract: Objective Enhanced recovery after surgery (ERAS) pathways have previously been shown to be feasible and safe in elective spinal procedures. As publications on ERAS pathways have recently emerged in elective neurosurgery, long-term outcomes are limited. We report on our 18-month experience with an ERAS pathway in elective spinal surgery. Methods A historical cohort of 149 consecutive patients was identified as the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…These data are consistent with previous studies, indicating that implementation of ERAS could successfully reduce opioid use in the postoperative period without negatively increasing pain scores. 12 , 34 , 35 Our results also suggest that ERAS protocols in spinal surgery are safe. A non-significant decrease in complications was observed in the ERAS group compared with the pre-ERAS group (2 vs 3, respectively; p = 0.627).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These data are consistent with previous studies, indicating that implementation of ERAS could successfully reduce opioid use in the postoperative period without negatively increasing pain scores. 12 , 34 , 35 Our results also suggest that ERAS protocols in spinal surgery are safe. A non-significant decrease in complications was observed in the ERAS group compared with the pre-ERAS group (2 vs 3, respectively; p = 0.627).…”
Section: Discussionsupporting
confidence: 62%
“…Postoperative opioid consumption was significantly reduced in the ERAS group, as was hospital LOS. 12 In 2020, Yang et al studied the clinical outcomes of ERAS protocols for minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). The results suggest that ERAS protocols decrease hospital LOS and provide relief from back pain.…”
Section: Introductionmentioning
confidence: 99%
“…For one, ERAS has been shown to be more cost effective than traditional care approaches. 3 , 13 , 19 , 20 It has also been found to significantly reduce LOS 3 , 8 , 9 , 10 , 13 , 14 , 19 , 21 , 22 , 23 , 24 , 25 , 26 length of intensive care unit stay, 3 , 19 postoperative pain scores, 9 , 20 , 21 amount of opioids used postoperatively in the hospital, 9 , 12 , 21 , 22 , 23 , 27 , 28 and postoperative catheterization. 22 , 26 , 27 Evidence also suggests that ERAS in spine surgery may reduce the amount of rescue antiemetic medications used, 29 readmission rate, 25 , 30 and reoperation rate.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Accordingly, several studies suggest opioid-sparing strategies may be associated with lower rates of opioid-related adverse effects, including nausea, vomiting, sedation, urinary retention, and constipation. 24 , 30–36 Reduced consumption of opioids does not appear to negatively impact patient-reported pain or satisfaction levels and, in some studies, is associated with improved patient-reported pain scores. 25–31 , 34–38 The effect of opioid-sparing strategies during the acute postoperative period on chronic opioid use remains unclear, with some studies demonstrating a reduction of longer term opioid use while others showing no difference.…”
Section: Opioid Medicationsmentioning
confidence: 98%
“… 25–31 , 34–38 The effect of opioid-sparing strategies during the acute postoperative period on chronic opioid use remains unclear, with some studies demonstrating a reduction of longer term opioid use while others showing no difference. 30 , 38–43 Although opioid-sparing postoperative analgesic interventions have clear advantages with respect to reduced adverse effects and some studies even suggest that opioid medications may provide superior analgesia for acute pain compared to non-opioid therapies, the feasibility of opioid-free postoperative analgesia remains controversial and additional research in this area is needed. 44–46 …”
Section: Opioid Medicationsmentioning
confidence: 99%